2022
DOI: 10.1111/cyt.13178
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of the College of American Pathologists guideline for validating whole slide imaging for diagnostic purposes to cytopathology

Abstract: Whole slide imaging (WSI) allows pathologists to view virtual versions of slides on computer monitors. With increasing adoption of digital pathology, laboratories have begun to validate their WSI systems for diagnostic purposes according to reference guidelines. Among these the College of American Pathologists (CAP) guideline includes three strong recommendations (SRs) and nine good practice statements (GPSs). To date, the application of WSI to cytopathology has been beyond the scope of the CAP guideline due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…A recent large meta‐analytical studied showed that out of 25 studies on cytopathology, 4 (16%) studies followed the strong recommendations and only one (4%) study followed both strong and good practice guidelines of CAP. The authors concluded that rigorous and well‐designed studies on cytology are needed to generate robust evidences for the successful implementation of the WSI for the primary diagnosis in cytology 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large meta‐analytical studied showed that out of 25 studies on cytopathology, 4 (16%) studies followed the strong recommendations and only one (4%) study followed both strong and good practice guidelines of CAP. The authors concluded that rigorous and well‐designed studies on cytology are needed to generate robust evidences for the successful implementation of the WSI for the primary diagnosis in cytology 25 …”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that rigorous and well-designed studies on cytology are needed to generate robust evidences for the successful implementation of the WSI for the primary diagnosis in cytology. 25…”
Section: Guidelines For the Use Of Wsimentioning
confidence: 99%
“…These studies honored various Recommendations and Good Practice Statements proposed for digital system assessment and validation. 32 , 33 , 34 Accordingly, concurrent with formal clinical trials and system deployment in the clinical setting, BestCyte may be subjected to a rigorous suite of exercises relative to known cases and diagnoses involving primary screening and senior reviewer cytologists (i.e., cytotechnologists) and pathologists, 35 , 36 and the quality control and assurance workflows applicable in diagnostic practice. All abnormal cases in the 500 ThinPrep PCS were formally reported by a pathologist in 2016.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review of papers dealing with the validation of cytology for use in digital analysis showed that only a minority of the published papers followed all CAP recommendations, including both SRs and GPSs. 14 Since the present study investigated the implementation of the digital analysis of cytological samples in a CAP-accredited laboratory, all processes had to be performed rigorously, following CAP recommendations. As previously stated, because these recommendations do not address specific cytopathological issues, adjustments were made to allow for the practical considerations associated with the analysis of cytological samples, such as defining agreement and final concordance rates.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] It has been widely used for telecytology and rapid on-site evaluation, 9,10 but few papers have compared actual diagnoses obtained using whole slide images (WSIs) with those obtained using glass slides [11][12][13] , and even fewer have followed the CAP guidelines for the validation of WSI in a clinical setting. 14 In the current study, we aimed to validate different types of cytological preparations for routine clinical use in digital pathology, following the 2021 CAP guidelines, and also to highlight specific characteristics and difficulties involved in the use of such preparations in clinical everyday digital sign-out.…”
mentioning
confidence: 99%